Synthesis of Titanium Dioxide (TiO2) Fine particle by Flame Spray Pyrolysis (FSP) Method using Liquid Petroleum Gas (LPG) as Fuel - Hendri Widiyandari; Agus Purwanto; Vincensius Gunawan; Susilo Adi Widyanto (Dept. of Chemical Engineering, Diponegoro University, 2017)
This study aims to obtain titanium dioxide (TiO2) fine particle with a narrow size distribution by one step production via flame spray pyrolysis (FSP) using LPG (liquid petroleum gas) as a fuel source. The TiO2 particles were synthesized from the aqueous based precursor from dissolving of titanium (IV) isopropoxide to the acidic distilled water solvent. The effect of precursor concentration to the crystalline structure, morphology and size distribution of the TiO2 particles were systematically investigated. There were observed that the TiO2 has a uniform spherical shape with particle size around 200 – 500 nm. Increasing the precursor concentration resulted the size distribution shifted toward the bigger size. The crystalline structure of produced TiO2 showed the mixed phase of anatase and rutile and has a large specific surface area 850,343 m²/g.